Failure criteria assessment of carbon/epoxy laminate under tensile loads using finite element method: Validation with experimental tests and fractographic analysis - Marques, Bruno Mikio Fujiwara [UNESP]; Marques, Thaís Peres Zanetine; Silva, Fernando de Azevedo [UNESP]; Cândido, Geraldo Maurício; Rezende, Mirabel Cerqueira (Taylor & Francis, 2022)
The failure of polymer composites is complex due to the independent and interacting damage mechanisms. The availability of several failure criteria demands a reasonable discernment of each criterion in order to obtain a consistent response to make an assertive selection. The importance of this decision is present in simulation works using finite element method and it is of particular interest of the industry and designers, once an optimized project is the goal. This study regards a carbon/epoxy laminate based on plain weave fabric subjected to tensile load and numerical simulations using finite element method was applied to compare the widely used Maximum Stress, Tsai-Wu, Hoffman, Tsai-Hill, Hashin and Puck failure criteria. Experimental tensile tests were carried out and fractographic analysis was performed in order to validate the finite element model and the applicability of the failure criteria. The model presented a good agreement with the experimental results and the correlation between the fractographic analysis and the failure criteria results allowed to select the Puck criterion as the proper and adequate for the studied composite laminate subjected to tensile load.
Keywords: CFRP; Failure criteria; finite element analysis; fractography; polymer-matrix composites